Defective Autophagy and Mitophagy in Aging and Alzheimer’s Disease - Tran, Michael; Reddy, P. Hemachandra (Frontiers in Neuroscience, 2021)
Aging is the time-dependent process that all living organisms go through characterized by declining physiological function due to alterations in metabolic and molecular pathways. Many decades of research have been devoted to uncovering the cellular changes and progression of aging and have revealed that not all organisms with the same chronological age exhibit the same age-related declines in physiological function. In assessing biological age, factors such as epigenetic changes, telomere length, oxidative damage, and mitochondrial dysfunction in rescue mechanisms such as autophagy all play major roles in biological aging. Recent studies have focused on autophagy dysfunction in aging, particularly on mitophagy due to its major role in energy generation and reactive oxidative species generation of mitochondria. Mitophagy has been implicated in playing a role in the pathogenesis of many age-related diseases, including Alzheimer’s, Parkinson’s and Huntington’s. The purpose of our article is to highlight the mechanisms of autophagy and mitophagy and how defects in autophagy and mitophagy contribute to the physiological markers of aging. This article will also discuss how mitochondrial dysfunction, abnormal mitochondrial dynamics, and impaired biogenesis are related to aging and AD pathogenesis.